Let g(x)=x-3. Find a function f so that f(g(x))= Let f(x)= . Find a function g so that f(g(x))= Thanks!
Follow Math Help Forum on Facebook and Google+
Originally Posted by johett Let g(x)=x-3. Find a function f so that f(g(x))= We know that Assume we have a function f(x). Then f(x - 3) is a translation of this function 3 units to the right. And we know this function is . So if we translate the function f(x - 3) by 3 units to the left, we get f(x). So -Dan
Originally Posted by johett Let f(x)= . Find a function g so that f(g(x))= Since then we know the argument of must be . -Dan
Hello, johett! Let Find a function so that: . We want: . . . must transform into This can be done by: .adding 3 and squaring. Therefore: . Let . Find a function so that: . We want: . Therefore: .
View Tag Cloud